INTERNATIONAL EXPERIENCE OF TOTALITARY MODES AND INSTALLING CRIMINAL RESPONSIBILITY FOR THEIR PROPAGAND - Marchuk, Makar P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the main task of this scientific research is to study the international experience of condemnation totalitarian regimes. The article also covers the issues of criminal responsibility prosecution for the propagation of totalitarian regimes in European countries and in Ukraine. Methods: the using of international experience to improve blighty legislation, providing criminal responsibility for a perpetration. Results: suggestions for the prevention of totalitarian regimes renewal, which resulted in violations of civil rights, as one of the priorities of state political people, aimed to protect national interests and to insure Ukrainian citizens in safety. Discussion: based on comparison of the main international regulations issues aimed to totalitarian regimes conviction, harmonization of the norms of national criminal legislation with international norms and standards in the relevant sphere.